Paritaprevir/ritonavir/ombitasvir plus dasabuvir in HIV/HCV-coinfected patients with genotype 1 in real-life practice. Issue 1 (2nd January 2018) - Pineda, Juan A.; Rivero-Juárez, Antonio; de los Santos, Ignacio; Collado, Antonio; Merino, Dolores; Morano-Amado, Luis E.; Ríos, María J.; Pérez-Pérez, Montserrat; Téllez, Francisco; Palacios, Rosario; Pérez, Ana B.; Mancebo, María; et al.
Abstract : Background: Data on the efficacy, safety, and concomitant use with other drugs of the combination ritonavir-boosted paritaprevir/ombitasvir plus dasabuvir (PrOD) in HIV/HCV-coinfected patients in real life are limited. The objectives of this study were to analyze these topics in HIV/HCV-coinfected subjects bearing HCV genotype 1 (GT1). Methods: One hundred and eighty-two HIV/HCV-coinfected patients with GT1 (87 1a, 71 1b, 23 other) treated with PrOD, plus ribavirin (RBV) in 119 cases, in routine clinical practice were analyzed. The main variable of efficacy was sustained virological response (SVR) 12 weeks after completing therapy in an intention-to-treat (ITT) analysis and that of safety treatment discontinuation because of adverse effects. Factors associated with SVR were analyzed with a modified ITT (mITT) strategy. Results: One hundred and seventy-two (94%) patients attained SVR, 3 (2%) experienced a relapse and two (1%) discontinued therapy due to adverse events. The rates of SVR in subjects with GT 1a and 1b by mITT were, respectively, 97% and 98%. Sixty-five (98%) out of 66 patients with cirrhosis and 107 (98%) out of 110 ( p  = 1) non-cirrhotics achieved SVR. Fifty-five (95%) patients on concomitant darunavir therapy developed SVR vs. 117 (99%) ( p  = 0.105) of those without DRV. RBV dose was reduced in 13 (11%) patients and permanently discontinued in 2 (2%), with no impact on SVR. Conclusions: PrOD is highly effective and well tolerated in HIV/HCV-coinfected patients with GT1 in routine clinical practice. RBV is often required. However, RBV dose reduction or discontinuation is uncommonly needed and do not impair the SVR rate.